The Response of Rice Planting Area to Rice Availability in South Sumatra, Indonesia - Muhammad Yamin; Siti Ramadani Andelia; Selly Andini; Meitry Firdha Tafarini; Idham Alamsyah (Business Review and Case Studies, 2023)
South Sumatra has succeeded in meeting local rice needs. Nonetheless, rice production in South Sumatra has not been able to significantly contribute to meeting the ever-growing needs of Indonesia's population. Therefore, the government is always trying to increase rice production by increasing productivity and expanding the rice planting area. Rice is not only an economic good, but has become a political item. Therefore, government intervention is quite intense in stabilizing the availability of rice. One of the interventions carried out by the government of South Sumatra is targeting the planting area as a response to the availability of rice in the previous year. The purpose of this study was to analyze the response of planting area at the farmer level to changes in rice availability and supply elasticity in South Sumatra by using the previous year's planted area and the availability of rice from South Sumatra as determining indicators. The method used in this study is multiple linear regression using secondary data over a period of 20 years. The results show that the availability of rice in South Sumatra significantly affects the area planted with an elastic supply elasticity. Therefore, government programs such as printing new land or adding planting area (LTT), land optimization through increasing the planting index, and using abandoned land are urgently needed to support sustainable rice self-sufficiency in South Sumatra. Keywords: availability of rice, planting area, supply elasticity, South Sumatra